Estudo da diversidade de Sardinella brasiliensis (Steindachner, 1879), na área entre Macaé (22º23'S) e Ilha de Santa Catarina (27º35'S): 1. Crescimento de dimensões corporais - Braga, Francisco Manoel de Souza [UNESP] (Sociedade Brasileira de Zoologia, 1987)
The growth of body proportions of Sardinella brasiliensis was not homogeneous in the study area, between Macaé (RJ) and Santa Catarina Island (SC); the growth rates (K) of the von Bertalanffy growth curve were greater than growth rates for another áreas. In this area the biomass estimates for pelagic fish is poor, and near Cabo Frio occurs an upwelling zone. These facts permit the sardines to attain large lengths in this area. Between Rio de Janeiro and Florianópolis the growth rates were lower than in the northern part and Paranaguá Bay. on the other hand the biomass estimates for pelagic fish in Rio de Janeiro-Florianópolis region was very high, and in this zone the population density is high and the growth rates are small. Paranaguá Bay is a particular region because of its geographical and oceanographic conditons; this is a shelter region with different features and the sardines living there attain small length. In this area the growth rates are intermediary among growth rates for fishes from Macaé-Cabo Frio and Rio de Janeiro-Florianópolis regions. Therefore, the growth rates for sardines in southeast Brazilian proves to be dependent of the population density, food and oceanographic conditions.